Daya Terima dan Kandungan Gizi Kue Lidah Kucing yang Disubstitusi Tepung Sorgum dan Penambahan Daun Kelor (Moringa Oliefera) sebagai Alternatif Camilan Wanita Usia Subur (WUS) Anemia - Alby Tirtaarum Hari Paraswati; Rita Ismawati (Antigen : Jurnal Kesehatan Masyarakat dan Ilmu Gizi, 2025)
Anemia is one of the nutritional problems that can occur in women of childbearing age (WUS). One effort that can be made is to consume foods that are sources of iron, such as sorghum and moringa leaves. Utilization that can be done by substituting sorghum flour and adding moringa leaves. This study aims to determine the effect of the acceptability and nutritional content of cat's tongue cookies substituted with sorghum flour and the addition of moringa leaves as an alternative snack for women of childbearing age with anemia. This type of research is a pure experimental study with the Completely Randomized Design (CRD) method, the comparison used is sorghum flour 25%, 50%, 75% and moringa leaves 10%, 15%. Data collection using an acceptability test questionnaire conducted by 30 panelists. Data analysis using the Kruskal Wallis test and the Mann Whitney follow-up test. The results showed that this cat's tongue cookie affected the acceptability including color, shape, aroma, texture, and taste. This study resulted in the selected formula being F1 with 25% substitution of sorghum flour and 10% addition of moringa leaves. The best nutritional content of cat tongue cake per 100 g consists of 12.50% protein, 2.37 mg iron, and 9.37 mg vitamin C. This selected formula cat tongue cake can be used as an alternative snack for women of childbearing age (WUS) with anemia.